Respuesta :
Answer:
b = 1 - a
Step-by-step explanation:
Given
7 + 7a = 7(2 - b) ← divide both sides by 7
1 + a = 2 - b ( subtract 2 from both sides )
- 1 + a = - b ( multiply through by - 1 )
1 - a = b
Answer:
[tex]b = (a - 1)[/tex]
Step-by-step explanation:
Question
[tex]7 + 7a = 7(2 - b)[/tex]
First Solve the brackets
[tex]7 + 7a = 7(2 - b) \\ 7 + 7a = 14 - 7b[/tex]
Then Make the b as the Subject
[tex]7 + 7a = 14 - 7b \\7 + 7a - 14 = 7b \\ 7a - 7 = 7b \\ 7(a - 1) = 7b \\ \frac{7(a - 1)}{7} = \frac{7b}{7} \\ a - 1 = b[/tex]
hope this helps you.
Have a nice day!